Proses Penyelesaian Perselisihan Hubungan Industrial Melalui Pengadilan Hubungan Industrial Menurut Undang-Undang 2 Tahun 2004 Tentang Penyelesaian Perselisihan Hubungan Industrial - Suandi, Suandi; Fitri Ida Laela (Desanta Publisher, 2024)
The PHI Cassation petition is the last legal remedy to challenge an Industrial Relations Court decision that is not final, with direct submission to the Supreme Court (MA) within 14 working days. This cassation requires a Cassation Memorandum containing reasons for objection and is adjudicated by the Cassation Panel of Judges. Judicial Review (PK) is a mechanism to correct PHI decisions that have been finalized if falsehoods, new evidence, or judge errors are found, with a case fee of Rp.2,500,000 and a deadline of 180 days. The Supreme Court's decision on cassation and review can be in the form of rejection, annulment, or retrial.